Building indicators to address community sustainability: learning from the Mixteca region, Mexico. Issue 6 (17th August 2016) - Gutiérrez, M. Delia; Manzano, Mario G.; García, Melba D.; Foucrás, Nicolás; Osorio, Francisco J.; Carbajal-Morón, Nallely A.; Porsen, Rena; Villarreal, Luis
ABSTRACT: This article reports on an indicator model to assess sustainability at the community level that was developed by an interdisciplinary work group. We applied this model in a case study of the Mixteca region in Oaxaca, Mexico, and provided a tool guide to measure the effectiveness of community-based actions. Two innovative aspects are presented: an iterative process with the community to develop a locally appropriate set of indicators drawn from the literature, and a baseline diagnostic assessment of the community's performance on these indicators. This assessment may serve as a basis for future research and community-driven projects.